The Emergence of Rare Clinical Aspergillus Species in Qatar: Molecular Characterization and Antifungal Susceptibility Profiles - Salah, Husam; Lackner, Michaela; Houbraken, Jos; Theelen, Bart; Lass-Flörl, Cornelia; Boekhout, Teun; Almaslamani, Muna; Taj-Aldeen, Saad J. (Frontiers in Microbiology, 2019)
Aspergillus are ubiquitous mold species that infect immunocompetent and immunocompromised patients. The symptoms are diverse and range from allergic reactions, bronchopulmonary infection, and bronchitis, to invasive aspergillosis. The aim of this study was to characterize 70 Aspergillus isolates recovered from clinical specimens of patients with various clinical conditions presented at Hamad general hospital in Doha, Qatar, by using molecular methods and to determine their in vitro antifungal susceptibility patterns using the Clinical and Laboratory Standards Institute (CLSI) M38-A2 reference method. Fourteen Aspergillus species were identified by sequencing β-tubulin and calmodulin genes, including 10 rare and cryptic species not commonly recovered from human clinical specimens. Aspergillus welwitschiae is reported in this study for the first time in patients with fungal rhinosinusitis (n = 6) and one patient with a lower respiratory infection. Moreover, Aspergillus pseudonomius is reported in a patient with fungal rhinosinusitis which is considered as the first report ever from clinical specimens. In addition, Aspergillus sublatus is reported for the first time in a patient with cystic fibrosis. In general, our Aspergillus strains exhibited low MIC values for most of the antifungal drugs tested. One strain of Aspergillus fumigatus showed high MECs for echinocandins and low MICs for the rest of the drugs tested. Another strain of A. fumigatus exhibited high MIC for itraconazole and categorized as non-wild type. These findings require further analysis of their molecular basis of resistance. In conclusion, reliable identification of Aspergillus species is achieved by using molecular sequencing, especially for the emerging rare and cryptic species. They are mostly indistinguishable by conventional methods and might exhibit variable antifungal susceptibility profiles. Moreover, investigation of the antifungal susceptibility patterns is necessary for improved antifungal therapy against aspergillosis.